How to Set Up A Cash Buffer : A Practical Guide to Developing and Implementing a Cash Buffer Policy - Hurcan, Yasemin (IMF How To Notes; How-To Note ;, 2020)
Maintaining a cash buffer has emerged as a risk management tool for government cash and debt management. During budget execution, there is considerable cash flow volatility and timing mismatches concerning revenue collections and expenditures, debt inflows, and debt service. Cash balance management aims to address these mismatches and to ensure availability of liquidity in government bank accounts. From a debt management perspective, holding an appropriate level of cash balance serves to mitigate funding risk. Effective cash balance management is even more critical when there is heightened uncertainty about the magnitude and timing of cash flows, as seen during the coronavirus disease (COVID-19) pandemic. This note discusses the role of the cash buffer for managing cash balances and offers practical approaches to developing a policy framework, considering the risk mitigation objectives and the cost of carry.